From Dorms to Dining Tables: How Social Support Influences PCOS Management in College Students - Simar kaur; Dr. Saumya Sharma (The Bioscan, 2025)
Polycystic Ovary Syndrome (PCOS) is a multifaceted condition that affects both physiological and psychological well-being, ultimately affecting the quality of life. This study aims to explore the importance of family support in the management of socio-emotional symptoms of PCOS in college students, particularly by comparing the experiences of students living with family and those who live independently in and around the college campus. The Polycystic Ovary Syndrome Questionnaire (PCOSQ) provided quantitative data for this mixed-methods study, while in-depth interviews provided qualitative insights. Emotional health, body hair, weight, infertility, and irregular menstruation were all evaluated by the PCOSQ. 34 college students with PCOS were included in the sample. 10 participants also participated in semi-structured interviews, which uncovered themes like the relevance of peer and community connections in lowering emotional isolation, the usefulness of family support, and challenges in independently managing PCOS-related stress. When taken as a whole, the results provide a thorough picture of young adult PCOS. The results revealed noteworthy findings where students who lived with family members reported significantly higher quality of life scores. Participants living with family underscored the value of consistent shared responsibility for health management and highlighted access to nutritious home-cooked meals, which positively impacted their physiological symptoms. In contrast, those residing independently appreciated their autonomy and, while facing challenges in practical support, reported receiving greater emotional support from friends and dorm mates than from family. The integration of quantitative and qualitative data provided a nuanced understanding of how familial social support affects the management of PCOS. These findings highlight the profound impact on how important social support, particularly from family, is in helping college students manage PCOS. To improve mental health and general quality of life, future initiatives should concentrate on family-centered interventions, peer support networks, and focused resources for independent learners.